Cytomorphological Spectrum of Tuberculous Lymphadenitis: A Comparative Study Between Pediatric and Adult Populations - Pandey, Deepika; Pradhan, Mohit; Paul, Rahul; Saha, Rama (Journal of Neonatal Surgery, 2025)
Background: The most prevalent kind of extrapulmonary tuberculosis is tuberculous lymphadenitis (TBL), which differs from pediatric to adult patients in both cytomorphology and clinical manifestations. Although fine-needle aspiration cytology (FNAC) is essential for early diagnosis, there is currently a dearth of age-group comparison data. Aim: To evaluate and compare the cytomorphological patterns tubercular lymph node lesions in the paediatric population with that of the adult population Materials and methods: This was a comparative study, 50 pediatric and 150 adult patients diagnosed with tubercular lymphadenitis were enrolled and analysed in this study. Cytology smears were retrieved, reviewed and analysed. Cytological diagnosis of tubercular lymphadenopathy was determine and compared between pediatric and adult population. Results: The lesions were most common (40% in 6-10 years in paediatric age and (40%) in 30-35 years in adult age group. Males were predominant in both paediatric (58%) and adult (56%) group. The cervical group of lymph nodes was the most frequently affected in both age groups. AFB positivity was more in pediatric TB lymphadenitis (75%) as compared to adult Tb lymphadenitis (54%). Reactive lymphadenitis was the commonest pattern followed by chronic lymphoproliferative lesions and mycobacterial lymphadenitis in both the groups. Cytomorphological pattern of tubercular lymphadenitis between pediatric and adult patients were differ significantly (p<0.05) Conclusion: Cytological evaluation of lymph node lesions has a high diagnostic efficacy for the diagnosis of neoplastic lesions. The findings contribute to refining diagnostic approaches and improving the overall management of this extrapulmonary manifestation of tuberculosis.